Cluster-Module As Method Of The Improvement Of The Current Direction In Structure Of The Section Of The Physical Culture (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The actuality of the research. Today in our country, special attention is paid to the development of physical culture and sports among students of higher educational institutions. The number of students studying in higher educational institutions of the Republic is increasing every year, and many of them are not ready to fully perform the loads of physical exercises set in the standard educational programs on the subject of "Physical culture and sports". This position requires the development of a new cluster-modular method aimed at improving the performance of students with different levels of physical development and physical fitness.